The book of Isaiah chapters I-XXXIX in the light of the Assyrian monuments - Boutflower, Charles, 1846- (London, UK Society for Promoting Christian Knowledge, 1930)
Includes bibliographical references, index and photographs.
Donated by Engadine Bible Centre, 2005
Keywords: Bible. O.T. Isaiah I-XXXIX -- commentaries; Bible. O.T. Isaiah I-XXXIX -- archaeological considerations